Numerical model of lightning attachment on UHV-AC transmission lines and effects of operating voltage, phase angle, and terrain - Ma, Ziwei; Jasni, Jasronita; Ab Kadir, Mohd Zainal Abidin; Azis, Norhafiz (Elsevier, 2024)
A numerical model for lightning attachment on UHV-AC double-circuit transmission lines was developed using the leader propagation method (LPM) and the finite element method (FEM). The striking distance (SD) of the ground wire (GW) was calculated based on this model. The effects of operating voltage, phase angle, and terrain on the electric field of the wires were also analyzed. The simulation results revealed that when the phase conductors were energized, upward leaders (ULs) simultaneously occurred on both the GW and the upper-phase conductor. The velocity of the GW UL was faster than that of the upper-phase UL, allowing it to successfully intercept the downward leader (DL) in the air, while the upper-phase UL aborted after propagating 1.8 m under the shielding effect of the GW UL. A new expression of rs=7.2Ip0.87 for calculating the SD on the GW was proposed based on the simulation results. This expression provided reasonable results that fell between those obtained from the electro-geometric models and the analytical model. Additionally, the simulation results demonstrated that extremely high voltage, phase angle, and terrain slope increased the surface electric field of the upper-phase conductor, thereby increasing the risk of shielding failure.